A fluorine-containing heterocycle-modified high-etching-resistance arf photoresist resin and a photoresist composition

CN122940939APending Publication Date: 2026-10-20广州市番禺区市桥李璟文日用杂货店
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611030854.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]1. 发明目的,克服现有 ArF 光刻胶树脂耐干法刻蚀性能弱、吸湿率高、图形边缘粗糙度大的缺陷,提供一种短链氟 - 金刚烷 - 三唑杂环三元协同改性共聚树脂,同时配套高稳定型光刻胶复配组合物;兼顾高耐刻蚀、低吸水、高图形精度、长储存周期四大核心性能指标,适配 28~55nm 国产半导体制程工业化量产

Benefits of technology

[0017]工业化量产工程说明,本发明梯度升温聚合工艺放热平缓,无爆聚风险,可直接由实验室 5L 小试反应釜放大至 500L 工业量产反应釜;量产批次树脂 Mw、PDI 性能波动幅度≤5%,批次稳定性高;整套制备、配胶、过滤工艺可直接适配现有国产光刻胶生产线,无需定制特种设备,原料均为国内精细化工厂商量产供应,产业化落地门槛低。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a fluorinated heterocyclic modified high-etch-resistant ArF photoresist resin and a photoresist composition. The resin adopts a ternary gradient temperature-increasing copolymerization structure of C2-C4 short-chain perfluoroalkyl monomers, adamantane alicyclic monomers, and 1,2,4-triazole heterocyclic monomers, combined with hindered phenol-fluorinated polyether compound functional additives to prepare a special 193nm chemically amplified photoresist. The ternary molecular configuration creates a synergistic effect, simultaneously improving the resin's dry etching resistance and reducing the film's water absorption rate. The edge roughness of the photolithographic pattern can be controlled to ≤1.2nm, and the finished product can be stored at room temperature in the dark for up to 18 months. High-temperature baking of the wafer results in no pinholes or shrinkage defects. This invention fills the gap in the overall performance of single modified ArF photoresist resins, achieving the domestic optimization and upgrading of core photoresist resins. It is suitable for mass production photolithography processes in 55nm-28nm semiconductor manufacturing, and has extremely high import substitution and patent licensing industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor photolithography materials technology, specifically involving an optimized formulation system for 193nm ArF dry photoresist copolymer resin, which is compatible with dry photolithography processes for 28nm~55nm logic chips and memory chips, and can be used for high-precision patterning of wafer contact holes and trenches. Background Technology

[0002] Currently, the mainstream commercial ArF photoresists adopt binary and ternary alicyclic copolymer resin systems, which generally suffer from three major shortcomings: Insufficient resistance to dry etching: The carbon backbone of the single adamantane alicyclic structure has limited density, and the carbon backbone is easily broken by active free radicals during plasma etching, resulting in severe loss and deformation of fine photolithographic patterns; High water absorption rate: The resin has a single polar group structure, and water vapor in the air is easily adsorbed and penetrates into the film layer, causing linewidth shift in the pattern after exposure and a significant increase in developing voids and bridging defects; Poor edge roughness of the pattern: The surface energy of pure alicyclic resin is relatively high, resulting in uneven interface distribution after spin coating. The edge roughness of conventional products is generally >2.0nm, which cannot meet the pattern control requirements of 28nm high-precision processes.

[0003] Existing improvement schemes only introduce alicyclic structures or fluorine modification individually. The industry has not yet publicly disclosed resin molecular structures that synergistically modify short-chain fluoroalkyl groups, adamantane alicyclic groups, and polar triazole heterocycles. Long fluoroalkyl segments are prone to phase separation from hydrocarbon resin matrices, and simply introducing heterocycles increases overall water absorption. Single alicyclic modification has limited impact on improving etching resistance. A balanced and synergistic technical system for these three structural types is lacking. Currently, China relies heavily on imports for core resins of high-end ArF photoresists, and there is a critical gap in domestic material technology for substitution. This invention achieves iterative optimization of the molecular structure based on existing copolymer resin synthesis systems, simultaneously addressing the aforementioned common pain points in the industry. Summary of the Invention

[0004] 1. Purpose of the invention: To overcome the shortcomings of existing ArF photoresist resins, such as weak dry etching resistance, high moisture absorption, and large pattern edge roughness, and to provide a short-chain fluorine-adamantane-triazole heterocyclic ternary synergistic modified copolymer resin, along with a matching high-stability photoresist composite composition; taking into account the four core performance indicators of high etching resistance, low water absorption, high pattern accuracy, and long storage cycle, and adapting to the industrial mass production of 28~55nm domestic semiconductor processes.

[0005] 2. Technical solution, (1) Fluorine-containing heterocyclic modified ArF photoresist copolymer resin

[0006] The raw material monomer composition is as follows: the resin is prepared by free radical gradient temperature copolymerization of three types of monomers. The molar ratio of the three types of monomers is as follows: 10-20 parts of C2-C4 short-chain perfluoroalkyl acrylate monomer, 60-70 parts of adamantyl methacrylate monomer, and 10-20 parts of 1,2,4-triazole heterocyclic vinyl monomer.

[0007] Short-chain perfluoroalkyl groups are limited to C2, C3, and C4 perfluoroalkyl groups to avoid the problems of resin matrix layering and poor component compatibility caused by long-chain perfluoroalkyl groups; adamantyl methyl methacrylate is selected from monoadamantane methyl methacrylate to provide a high-density saturated tricyclic carbon rigid skeleton for the molecular chain; triazole heterocyclic vinyl monomers are selected from ethylene monomers with 1,2,4-triazole structures suspended by side chains, and intramolecular hydrogen bond networks are constructed using heterocyclic polar groups to inhibit water molecule adsorption and permeation.

[0008] The polymerization process is complete and reproducible. The reaction atmosphere is maintained by continuous purging with high-purity nitrogen, ensuring the oxygen content in the reactor is controlled to <10ppm to prevent quenching of active centers in free radical polymerization. The initiator is azobisisobutyronitrile (AIBN), added at 2%~3% of the total monomer molar amount, with a preferred addition ratio of 2.5%. The gradient temperature-controlled segmented polymerization process involves initial holding at 80~90℃ for 4~5 hours, followed by a slow, uniform increase to 110~120℃ at a rate of 10℃ / h for 5~6 hours. The low-temperature stage allows for slow initiation and reduces molecular branching, while the high-temperature stage fully completes the chain growth reaction. The post-treatment purification process involves natural cooling to room temperature after polymerization, followed by methanol precipitation to obtain solid crude resin. The crude product is diluted with ethanol and passed through a cation exchange resin column to remove metal ions, then washed with deionized water for 3 minutes. Unreacted residual monomers were removed; the resin was vacuum dried at 60°C for 12 hours to obtain a solid copolymer resin; the total metal impurity content of the purified resin was less than 1 ppb, meeting the pollution control standards for advanced wafer fabrication processes; the core physical properties of the resin were: weight-average molecular weight Mw = 5000~15000, and molecular weight distribution index PDI ≤ 1.6.

[0009] Brief description of the monomer chemical structure: C2-C4 perfluoroalkyl acrylate: Main structural formula CH2=CH-COO-(CF2) n CF3 (n=1, 2, 3); adamantyl methacrylate: methacrylate functional group side-bonded to a saturated adamantane tricyclic carbon skeleton; triazole heterocyclic ethylene monomer: vinyl group directly covalently bonded to a five-membered 1,2,4-triazole heterocycle, the heterocycle only serves as a side chain dangling group and does not form a large-scale conjugated structure.

[0010] (2) The photoresist composition formulation system is composed of the above-mentioned ternary copolymer resin, photoacid generator suitable for 193nm light source, compound functional additives, and organic solvents. The total mass of the composition is 100%: ternary copolymer resin: 15~25 wt%; photoacid generator: 2~5 wt%; functional compound additives: 0.6~2.5 wt%; organic solvent: to make up to 100 wt%.

[0011] Detailed component supplementation: Photoacid generator: any one of perfluoroalkyl sulfonate type triarylthioonium salts or diaryliodonium salts whose absorption peak matches the 193nm ArF light source; Functional additives: hindered phenolic antioxidant + fluorinated polyether nonionic surfactant, with a mass ratio of 1:2 to 1:10, and an optimal stable ratio of 1:4 to 1:6; The hindered phenol captures free radicals in the system, inhibiting the thermo-oxidative aging of the resin; The fluorinated polyether reduces the surface tension of the film layer and improves the coating uniformity; Organic solvent: propylene glycol methyl ether acetate (PGMEA), cyclopentanone, ethyl lactate, or any mixture of two solvents.

[0012] The photoresist preparation process involves stirring and dissolving all components for 8 hours in a cleanroom environment under ambient temperature and yellow light. The mixture is then sequentially filtered through two 0.2μm polytetrafluoroethylene (PTFE) membranes and stored in a light-protected, sealed, and temperature-controlled environment. This photoresist is a 193nm chemically amplified positive-type photoresist: in the exposed areas, the photoacid generator decomposes to produce a strong acid, which, after being baked at 100-130℃ for 60-90 seconds using PEB, activates the polar groups of the catalytic resin, allowing for rapid dissolution in a 2.38% TMAH alkaline developer. In the unexposed areas, the hydrophobic molecular chain structure is stable and difficult to dissolve in the developer, thus enabling precise transfer of wafer patterns.

[0013] 3. Beneficial effects and the scientific mechanism of synergistic effect of ternary components

[0014] Adamantane binary resin alone lacks a low-surface-energy hydrophobic structure, resulting in poor edge roughness of the lithographic pattern; fluorine-modified binary resin alone lacks a hydrogen-bonded water-blocking structure, leading to high water absorption of the film; heterocyclic binary resin alone has insufficient carbon skeleton density, resulting in weak resistance to plasma etching. This invention, through the simultaneous copolymerization of three types of monomers, covalently bonds three functional groups to the main molecular chain, forming a three-dimensional interlocked molecular configuration of "rigid carbon anti-etching skeleton - low-surface-energy fluorine side chain - hydrogen-bonded water-blocking heterocyclic side group": the adamantane unit relies on high-density C / C bonds to resist plasma free radical bombardment, improving etching tolerance; short-chain fluoroalkyl groups are uniformly dispersed at the resin film interface, reducing surface energy, eliminating coating agglomeration defects, and optimizing pattern edge roughness; 1,2,4-triazole heterocycles construct a continuous hydrogen bond network within the molecule, forming a hydrophobic barrier within the film, preventing the adsorption of external water molecules. These three structures mutually constrain each other at the molecular scale, avoiding the inherent shortcomings of single modification schemes and producing a synergistic effect beyond the simple superposition of single components. Supplementing the photochemical stability mechanism: 1,2,4-triazole is only a short conjugated heterocyclic ring with a suspended side chain, which will not undergo neutralization and quenching reactions with the photogenerated strong acid generated during exposure, and will not reduce photosensitivity; at the same time, the weak polarity of the heterocycle can moderately buffer the diffusion rate of acid in the film and suppress the linewidth shift of the pattern caused by excessive diffusion of strong acid.

[0015] Quantitative performance indicators and standardized testing conditions: Atomic force microscopy (AFM) was used to test the edge roughness of the pattern; inductive gravimetric method was used to test the water absorption rate according to GB / T 1034-2008 standard; inductively coupled plasma etching machine was used to test the dry etching rate with standardized parameters; constant temperature and humidity chamber at 25℃ and 60% humidity was used to test the moisture absorption performance; and 60℃ constant temperature accelerated aging was used to test the storage stability.

[0016] Dry etching resistance: Compared with traditional binary adamantane resin, the resin's etching tolerance is improved by more than 30% under the same etching parameters, and the etching loss of the exposure pattern is significantly reduced; Water absorption: After standing in a room temperature environment of 25℃ and 60% humidity for 24 hours, the resin's water absorption is reduced by 50% compared with existing binary resins; Pattern edge roughness: After photolithography, PEB baking, and development, the pattern edge roughness is ≤1.2nm, which is better than the 2.0nm control standard of conventional products on the market; Storage stability: No delamination or solid precipitation after 18 months of sealed storage at room temperature away from light; No pinhole defects after 30 days of accelerated aging at 60℃, and the photosensitivity decay is <3%; Coating uniformity: After spin coating of the entire 8-inch wafer, the film thickness error is ≤1%, and there are no pinhole or shrinkage defects after high-temperature curing and baking at 140℃.

[0017] The industrial mass production engineering description shows that the gradient temperature polymerization process of this invention has a gentle exothermic effect and no risk of explosive polymerization. It can be directly scaled up from a 5L laboratory pilot reactor to a 500L industrial mass production reactor. The performance fluctuation of the resin Mw and PDI in the mass production batches is ≤5%, with high batch stability. The entire preparation, formulation, and filtration process can be directly adapted to existing domestic photoresist production lines without the need for customized special equipment. The raw materials are all supplied in large quantities by domestic fine chemical manufacturers, and the threshold for industrialization is low.

[0018] Specific embodiments, Example 1 (intermediate preferred ratio): Monomer molar ratio: 15 mol C3 perfluoroalkyl acrylate, 65 mol adamantyl methacrylate, 20 mol triazole heterocyclic ethylene monomer; Polymerization process: nitrogen-free oxygen protection, AIBN initiator addition of 2.5 mol%, initial temperature of 85℃ for 4 h, uniform temperature rise to 110℃ and hold for 6 h; methanol precipitation, ion exchange demetallization, water washing, vacuum drying at 60℃ to obtain solid resin; Mw=8200, PDI=1.32, total metal impurity content of 0.6 ppb; Photoresist preparation: 20 wt% copolymer resin, 3 wt% triarylthionium salt photoacid generator, 0.4 wt% hindered phenol antioxidant, 0.8 wt% fluorinated polyether surfactant (additive ratio 1:4 optimal range), the remaining solvent is pure PGMEA; stirring at room temperature in the dark for 8 h, two 0.2 μm PTFE filters to obtain the finished photoresist.

[0019] Example 2 (Upper Limit of Fluorine Monomer Ratio) Monomer Molar Ratio: 18 mol of C2 perfluoroalkyl acrylate, 62 mol of adamantyl methacrylate, and 20 mol of triazole heterocyclic ethylene monomer; Polymerization Process: Initially held at 80℃ for 5 h, then uniformly heated to 115℃ for 5 h; After complete purification, the resin Mw=9100 and PDI=1.41; Photoresist Composition: 22 wt% copolymer resin, 4 wt% diaryliodonium salt photoacid generator, 2.0 wt% total proportion of compound additives, and the balance is made up by a mixed solvent of PGMEA and cyclopentanone.

[0020] Example 3 (lower limit of formulation ratio): Monomer ratio: 10 mol C4 perfluoroalkyl acrylate, 70 mol adamantyl methacrylate, 20 mol triazole heterocyclic ethylene monomer; polymerization was carried out in a gradient temperature range of 80~110℃, with two-stage heat preservation polymerization. After purification, the resin had Mw=6100 and PDI=1.51; all performance indicators of the photoresist met the standards.

[0021] Example 4 (Upper Limit of Formulation Ratio): Monomer Ratio: 20 mol C2 perfluoroalkyl acrylate, 60 mol adamantyl methacrylate, 20 mol triazole heterocyclic ethylene monomer; Maximum isothermal range of polymerization: 120℃; Purified resin Mw=13500, PDI=1.55; Resin components have good compatibility and no stratification.

[0022] Comparative Example 1: Commercially available traditional binary adamantane resin (fluorine-free, heterocyclic-free), consisting only of adamantane methacrylate + general acrylate binary copolymer system, without introducing fluoroalkyl or triazole heterocycles; using the same photoresist formulation and testing conditions, the resin exhibits a 32% higher dry etching rate, a 51% higher 24-hour water absorption rate, a pattern edge roughness of 2.18 nm after development, and trace amounts of solid precipitation after only 8 months of storage at room temperature in the dark.

[0023] Comparative Example 2: A monofluoro-modified binary resin (without triazole heterocycles), a fluoroalkyl-adamantane binary copolymer resin, without 1,2,4-triazole heterocycle structures; under the same temperature and humidity test conditions, the resin water absorption rate was twice that of the sample of this invention, and water vapor penetration caused frequent wafer pattern linewidth offset defects.

[0024] Comparative Example 3: Fluorine-free heterocyclic binary resin (without short-chain fluoroalkyl groups), adamantane monomer + triazole heterocyclic binary copolymer, without the introduction of fluorine modification units; spin-coating film uniformity is poor, and the edge roughness of the pattern is 1.96nm, which cannot meet the high precision requirements of the 28nm process.

Claims

1. Claim 1. A fluorinated heterocyclic modified ArF photoresist resin with high etching resistance, characterized in that, The copolymer is composed of three monomers: an acrylate monomer containing a C2-C4 short-chain perfluoroalkyl group, a methacrylate monomer containing an adamantyl group, and a vinyl monomer containing a 1,2,4-triazole heterocycle; the molar ratio of the three monomers is (10~20):(60~70):(10~20); the weight average molecular weight of the copolymer resin is 5000~15000, and the molecular weight distribution index (PDI) is ≤1.

6.

2. The fluorine-containing heterocyclic modified high-etch-resistant ArF photoresist resin according to claim 1, characterized in that, The resin polymerization process is carried out under high-purity nitrogen oxygen-free protection, with AIBN as the free radical initiator, and the polymerization temperature range is 80℃~120℃, with a gradient segmented polymerization at a heating rate of 10℃ / h.

3. A method for preparing the fluorine-containing heterocyclic modified high-etch-resistant ArF photoresist resin according to any one of claims 1 to 2, characterized in that, The purification process includes gradient temperature free radical polymerization, methanol sedimentation for coarse separation, cation exchange resin for metal ion removal, deionized water washing, and vacuum drying. The total metal impurity content of the purified resin is less than 1 ppb.

4. A photoresist composition, characterized in that, It comprises the ArF photoresist resin as described in any one of claims 1 to 2, a photoacid generator adapted to a 193nm ArF light source, a functional compound additive, and an organic solvent.

5. The photoresist composition according to claim 4, characterized in that, The mass percentages of each component are as follows: copolymer resin 15~25 wt%, photoacid generator 2~5 wt%, functional additives 0.6~2.5 wt%, and organic solvent to make up to 100%.

6. The photoresist composition according to claim 4, characterized in that, The functional additive is a compound of hindered phenolic antioxidant and fluorinated polyether nonionic surfactant, with a mass ratio of 1:2 to 1:10, preferably 1:4 to 1:

6.

7. The photoresist composition according to claim 4, characterized in that, The photoacid-generating agent is a perfluoroalkyl sulfonate type triarylthioonium salt or a diarylioioonium salt; the organic solvent is selected from one or more of PGMEA, cyclopentanone, and ethyl lactate.

8. A wafer photolithography process, characterized in that, The photoresist composition according to any one of claims 4 to 7 is used to sequentially spin-coate, expose 193nm ArF, bake PEB, develop TMAH, and dry etch semiconductor wafers from 55nm to 28nm.

9. The wafer lithography process according to claim 8, characterized in that, After exposure, the PEB baking conditions are 100~130℃, and the baking time is 60~90s.

10. The application of the photoresist composition of claim 4 in the ArF dry lithography manufacturing process of 28nm~55nm logic chips and memory chips.